The oak gall wasps of Israel (Hymenoptera, Cynipidae, Cynipini)—diversity, distribution and life history - Shachar, Einat; Melika, George; Inbar, Moshe; Dorchin, Netta (Zootaxa, 2018)
Oak-galling wasps (Hymenoptera: Cynipidae, Cynipini) have been studied in Israel only superficially so far, despite interest in the Israeli fauna given its location at the southern edge of distribution range of the wasps and their oak hosts. We provide the first comprehensive review of the Israeli fauna of oak cynipids based on an extensive survey of the five naturally occurring oak species in Israel. We report 53 cynipid species, 37 of which are reported from Israel for the first time, 10 are currently known only from this country, and 9 are undescribed. With 27 species, Andricus is by far the biggest genus in Israel, followed by Cerroneuroterus, Neuroterus Plagiotrochus, and Pseudoneuroterus with 4 species each. Andricus megalucidus is synonymized under A. cecconii and Cerroneuroterus cerrifloralis is synonymized under C. lanuginosus. The sexual generations of Andricus cecconii, A. coriariformis, A. coriarius, A. miriami, Cerroneuroterus lanuginosus and Pseudoneuroterus macropterus are reported here for the first time. We recorded 65 gall types, with bud galls being the most common and conspicuous, followed by leaf and catkin galls. We provide illustrated keys for all Israeli species based on their galls, as well as information on host associations, life history, phenology and distribution patterns where available. 21 cynipid species are associated with Quercus ithaburensis and 27 species are associated with Q. boissieri, whereas Q. libani, Q. calliprinos and Q. cerris host much fewer species. Most species are currently known from either their sexual or asexual generation while only 24% of them are known from both. Mount Hermon was found to be an important hotspot, hosting about half of the Israeli cynipid fauna, and species richness generally declines from the Golan Heights southwards to the Judean Mountains. Cynipid species that are associated with oaks of sections Cerris and Quercus in Europe are mostly associated with the same sections in Israel.